2019
DOI: 10.1016/j.toxicon.2018.11.360
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underpinning the permanent muscle damage induced by snake venom metalloprotease

Abstract: Snakebite is a major neglected tropical health issue that affects over 5 million people worldwide resulting in around 1.8 million envenomations and 100,000 deaths each year. Snakebite envenomation also causes innumerable morbidities, specifically loss of limbs as a result of excessive tissue/muscle damage. Snake venom metalloproteases (SVMPs) are a pre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…4 a). Metalloproteases are important venom components of most venomous animals including cnidarians, where they can cause tissue degradation [ 31 , 72 , 91 ]. Metalloproteases, mostly belonging to the Astacin-like family, have previously been detected in the soluble nematocyst content of jellyfish, Hydra, sea anemones and corals [ 32 , 48 , 57 , 65 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 a). Metalloproteases are important venom components of most venomous animals including cnidarians, where they can cause tissue degradation [ 31 , 72 , 91 ]. Metalloproteases, mostly belonging to the Astacin-like family, have previously been detected in the soluble nematocyst content of jellyfish, Hydra, sea anemones and corals [ 32 , 48 , 57 , 65 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…from North and Central Americas are more abundant and have been widely investigated. These studies have shown hemostatic effects such as fibrino(geno)lytic and inhibition of platelet aggregation activities as well as local hemorrhage caused by degradation of the capillary basement membrane and muscle damage with lower regeneration [91][92][93]. As C. d. ruruima venom composition differs from other more prevalent C. durissus subspecies envenomings, an antivenom based on oligoclonal mixtures of antibodies could be a strategy to improve treatment.…”
Section: Snake Venom Metalloproteases (Svmps)mentioning
confidence: 99%
“…Moreover, although the low abundance of SVMP found in C. d. ruruima venom can be associated with rare cases of local sequelae, this group of toxins could be an additional factor for local injury as observed for North American Crotalus spp. venoms [93].…”
Section: Local Complications Such As Secondary Infections and Compartment Syndrome Seem To Appear At Very Low Frequency Inmentioning
confidence: 99%
See 1 more Smart Citation